1-(3-Mesityl-3-methylcyclobutyl)-2-(piperi-din1-yl)ethanone - Cukurovali, A; Özdemir, N; Yilmaz, I; Dinçer, M (Int Union Crystallography, 2005)
In the title compound, C21H31NO, the cyclobutane ring is puckered, with a dihedral angle of 25.74 (6)degrees. The mesityl and 2-N-piperidino-1-oxoethyl groups are in cis positions. The piperidine fragment adopts a chair conformation. Intermolecular C-(HO)-O-... interactions involving the piperidine CH group and the keto O atom lead to the formation of dimers, and intermolecular C-H-...pi interactions involving the cyclobutane CH group and the benzene ring are responsible for the formation of a two-dimensional network.
Keywords: Crystal